Geographical and temporal variation of injection drug users in Pakistan. (11th January 2013) - Archibald, Chris P; Shaw, Souradet Y; Emmanuel, Faran; Otho, Suleman; Reza, Tahira; Altaf, Arshad; Musa, Nighat; Thompson, Laura H; Blanchard, James F
Abstract : Objectives: We describe the characteristics of injecting drug users (IDU) in Pakistan in 2006 and 2011, and assess the heterogeneity of IDU characteristics across different cities and years as well as factors associated with HIV infection. Methods: Cross-sectional, integrated behavioural-biological surveys of IDU were conducted in 10 cities across Pakistan in 2006 and 2011. Univariate and multivariable analyses were used to describe the differences in HIV prevalence and risk behaviours between cities and over time. Results: Large increases in HIV prevalence among injection drug users in Pakistan were observed, with overall HIV prevalence increasing from 16.2% in 2006 to 31.0% in 2011; an increase in HIV prevalence was also seen in all geographic areas except one. There was an increase in risk behaviours between 2006 and 2011, anecdotally related to a reduction in the availability of services for IDU. In 2011, larger proportions of IDU reported injecting several times a day and using professional injectors, and fewer reported always using clean syringes. An increase in the proportion living on the street was also observed and this was associated with HIV infection. Cities differ in terms of HIV prevalence, risk profiles, and healthcare seeking behaviours. Conclusions: There is a high prevalence of HIV among injection drug users in Pakistan and considerable potential for further transmission through risk behaviours. HIV prevention programs may be improved through geographic targeting of services within a city and for involving groups that interact with IDU (such as pharmacy staff and professional injectors) in harm reduction initiatives.